Rescue of striatal long-term depression by chronic mGlu5 receptor negative allosteric modulation in distinct dystonia models. (1st July 2021) - Martella, G.; Bonsi, P.; Imbriani, P.; Sciamanna, G.; Nguyen, H.; Yu-Taeger, L.; Schneider, M.; Poli, S.M.; Lütjens, R.; Pisani, A.
Abstract: An impairment of long-term synaptic plasticity is considered as a peculiar endophenotype of distinct forms of dystonia, a common, disabling movement disorder. Among the few therapeutic options, broad-spectrum antimuscarinic drugs are utilized, aimed at counteracting abnormal striatal acetylcholine-mediated transmission, which plays a crucial role in dystonia pathophysiology. We previously demonstrated a complete loss of long-term synaptic depression (LTD) at corticostriatal synapses in rodent models of two distinct forms of isolated dystonia, resulting from mutations in the TOR1A (DYT1), and GNAL (DYT25) genes. In addition to anticholinergic agents, the aberrant excitability of striatal cholinergic cells can be modulated by group I metabotropic glutamate receptor subtypes (mGlu1 and 5). Here, we tested the efficacy of the negative allosteric modulator (NAM) of metabotropic glutamate 5 (mGlu) receptor, dipraglurant ( ADX48621 ) on striatal LTD. We show that, whereas acute treatment failed to rescue LTD, chronic dipraglurant rescued this form of synaptic plasticity both in DYT1 mice and GNAL rats. Our analysis of the pharmacokinetic profile of dipraglurant revealed a relatively short half-life, which led us to uncover a peculiar time-course of recovery based on the timing from last dipraglurant injection. Indeed, striatal spiny projection neurons (SPNs) recorded within 2 h from last administration showed full expression of synaptic plasticity, whilst the extent of recovery progressively diminished when SPNs were recorded 4–6 h after treatment. Our findings suggest that distinct dystonia genes may share common signaling pathway dysfunction. More importantly, they indicate that dipraglurant might be a potential novel therapeutic agent for this disabling disorder. Highlights: The mGlu5 receptor negative allosteric modulator dipraglurant exhibits a short half-life in rodents. Dipraglurant rescues long-term depression impairment in dystonia models. Chronic dipraglurant treatment is required to obtain a full plasticity rescue. mGlu5 receptors represent promising targets for the treatment of dystonia.